Rethinking research impact by Theology and Religious Studies with references to the Faculty of Theology at the University of Pretoria - Buitendag, Johan (Verbum et ecclesia, 2017)
TRS are two interconnected and mutually dependent fields of academic inquiry, which belong to the larger and more encompassing domain of general humanities. Given this interconnectivity, reciprocity, and interdependability as integrative part of the humanities, TRS find themselves in the same position of being constantly evaluated from various perspectives, including the particularly measurable aspect of research outputs. While research outputs can be measured rather easily in the sense that they are tangible and readable in a published format, the way they are actually evaluated and given credit for regarding their content is a totally different matter and a whole lot more complex a problem. This chapter is an attempt to demonstrate that research productions in the field of TRS should be evaluated not only against other completely different fields, such as natural sciences, but also against closer and more related domains from the very corpus of the Humanities. It is suggested, therefore, that three distinct features should be taken into account for a proper and fair assessment of research outputs in TRS: research productivity, citations, and academic reputation. These, in turn, must be always complemented by a set of necessarily subsequent measures such as an increased productivity reward, high citations reward, high impact journals must be rewarded, and international to be increased. The proposed ranking indicators and their rewarding measures are going to be discussed and exemplified with specific reference to the research performance of the FT within the UP, SA.